Investment decision and firm value: Moderating effects of corporate social responsibility and profitability of non-financial sector companies on the Indonesia Stock Exchange - Jaja Suteja; Ardi Gunardi; Erik Syawal Alghifari; Audrey Amelya Susiadi; Alfina Sri Yulianti; Anggi Lestari (Journal of Risk and Financial Management, 2023)
This study focused on increasing firm value through CSR- and profitability-moderated investment decisions in emerging markets. A panel data analysis method was used for this study with a total of 215 observations of non-financial sector companies on the Indonesian Stock Exchange from 2018 to 2020. The results of the Chow test and the Hausman test showed that the fixed effect model with GLS was the most feasible. The model showed that there was a negative effect of investment decisions on firm value and the role of CSR and profitability strengthened this effect. Based on the results of the robustness check, the research model remained consistent with the results of previous studies. Investment decisions have a negative effect on firm value, and CSR and profitability moderate this effect, either when using other control variables or when using a different estimation model, which in this case was quantile regression. Our findings provide an understanding of the fact that investment decisions are important financial decisions for companies and that they can be controlled through good fund management and risk management.
Keywords: 650; corporate social responsibility; emerging market; firm value; profitability; investment decision